Penetapan Kadar Vitamin B1 Pada Kacang Kedelai dan Tempe Yang Beredar di Pasar Raya Padang Secara Spektrofotometri Visibel - Fitra Fauziah; Roslinda Rasyid; Angga Prawina Akbar (Jurnal Farmasi Higea, 2016)
It has been the research about determination level of vitamin B1 in soy bean and tempe. The determination level of vitamin B1 was measured by spectrophotometry visible method. The result is level of vitamin B1 in soy bean higher than level of vitamin B1 in tempeh. Which level of vitamin B1 in soy bean and tempeh is about 1.0213 % ±0.0188% and 0.2960 % ±0.0095%. It show that the proces manufacturing, like washing, bathing, boiling can affect the level of vitamin B1. Statistic analyze anova one way by using SPSS 17 program shows there are significant different (p<0.05) in the level from each sample.